Kif13b Regulates PNS and CNS Myelination through the Dlg1 Scaffold. - Roberta Noseda; Marta Guerrero-Valero; Valeria Alberizzi; Stefano C Previtali; Diane L Sherman; Marilena Palmisano; Richard L Huganir; Klaus-Armin Nave; Ana Cuenda; Maria Laura Feltri; Peter J Brophy; Alessandra Bolino (PLoS Biology)
Microtubule-based kinesin motors have many cellular functions, including the transport of a variety of cargos. However, unconventional roles have recently emerged, and kinesins have also been reported to act as scaffolding proteins and signaling molecules. In this work, we further extend the notion of unconventional functions for kinesin motor proteins, and we propose that Kif13b kinesin acts as a signaling molecule regulating peripheral nervous system (PNS) and central nervous system (CNS) myelination. In this process, positive and negative signals must be tightly coordinated in time and space to orchestrate myelin biogenesis. Here, we report that in Schwann cells Kif13b positively regulates myelination by promoting p38γ mitogen-activated protein kinase (MAPK)-mediated phosphorylation and ubiquitination of Discs large 1 (Dlg1), a known brake on myelination, which downregulates the phosphatidylinositol 3-kinase (PI3K)/v-AKT murine thymoma viral oncogene homolog (AKT) pathway. Interestingly, Kif13b also negatively regulates Dlg1 stability in oligodendrocytes, in which Dlg1, in contrast to Schwann cells, enhances AKT activation and promotes myelination. Thus, our data indicate that Kif13b is a negative regulator of CNS myelination. In summary, we propose a novel function for the Kif13b kinesin in glial cells as a key component of the PI3K/AKT signaling pathway, which controls myelination in both PNS and CNS.